Targeted Delivery of Toxoplasma gondii Antigens to Dendritic Cells Promote Immunogenicity and Protective Efficiency against Toxoplasmosis - Lakhrif, Zineb; Moreau, Alexis; Hérault, Bruno; Di-Tommaso, Anne; Juste, Matthieu; Moiré, Nathalie; Dimier-Poisson, Isabelle; Mévélec, Marie-Noëlle; Aubrey, Nicolas (Frontiers in Immunology, 2018)
Toxoplasmosis is a major public health problem and the development of a human vaccine is of high priority. Efficient vaccination against Toxoplasma gondii requires both a mucosal and systemic Th1 immune response. Moreover, dendritic cells play a critical role in orchestrating the innate immune functions and driving specific adaptive immunity to T. gondii. In this study, we explore an original vaccination strategy that combines administration via mucosal and systemic routes of fusion proteins able to target the major T. gondii surface antigen SAG1 to DCs using an antibody fragment scFv directed against DEC205 endocytic receptor. Our results show that SAG1 targeting to DCs by scFv via intranasal and subcutaneous administration improved protection against chronic T. gondii infection. A marked reduction in brain parasite burden is observed when compared with the intranasal or the subcutaneous route alone. DC targeting improved both local and systemic humoral and cellular immune responses and potentiated more specifically the Th1 response profile by more efficient production of IFN-γ, IL-2, IgG2a and nasal IgA. This study provides evidence of the potential of DC targeting for the development of new vaccines against a range of Apicomplexa parasites.